The Genetic Basis of Congenital Cataracts: Advances in Diagnostics and Therapeutics - Starzyk, Agnieszka; Charzewski, Piotr (Quality in Sport, 2025)
Congenital cataracts, a significant cause of childhood blindness, result from genetic mutations, syndromic associations, and environmental factors, with autosomal dominant inheritance and mutations in genes like CRYAA and GJA8 being prevalent. This study reviewed literature from 2000 to 2023 on genetic etiology, surgical management, and emerging therapies. Genetic mutations in structural proteins such as crystallins and connexins account for over half of cases, emphasizing the critical role of early surgical intervention, particularly intraocular lens (IOL) implantation in children over two years old. Emerging approaches, including gene therapy and pharmacological interventions like small-molecule chaperones, hold promise for addressing underlying genetic causes. While surgical techniques and postoperative care have advanced, challenges like complications persist. Advances in genetic testing and innovative therapies are reshaping the field, offering the potential for improved outcomes and personalized treatments. Continued research is necessary to refine these strategies and enhance accessibility globally.